CanRisk-GP protocol: A feasibility study of incorporating proactive multifactorial breast cancer risk assessment into general practice - Francisca Stutzin Donoso; Stephanie Archer; Fiona M. Walter; Stephen Morris; Jon Emery; Jack Broome; Tim Carver; Joe Dennis; Lorenzo Ficorella; Amy Lafont; Adam E. Stokes; Laura Stylianou; et al. (PLoS ONE, 2025)
Background CanRisk is a risk assessment tool that implements the BOADICEA multifactorial breast cancer risk model. The BOADICEA model is recommended for use by the National Institute for Health and Care Excellence (NICE) in English, Welsh, and Northern Irish secondary/tertiary care to identify women who may be at moderate or high risk of developing breast cancer. BOADICEA combines information on cancer family history, demographic, lifestyle, hormonal risk factors and mammographic density with polygenic scores (PGS). Offering risk assessment using CanRisk in general practice has the potential to identify more women at moderate or high risk of developing breast cancer and improve their management and the appropriateness of referrals to secondary/tertiary care. Materials and methods In this feasibility study we plan to invite women aged 40–49 years from 5–8 practices across Cambridgeshire and Peterborough in England, UK to complete a breast cancer risk assessment using CanRisk via a newly developed public-facing version of the CanRisk tool and provide saliva samples for PGS. The study team will provide a risk report back to both the participants and their GP, with those women at above-population level risk advised to make an appointment with their GP to be referred to the clinical genetics service and subsequently managed in line with current NICE guidelines. This study will provide evidence on (1) whether offering cancer risk assessment including PGS in general practice is feasible and acceptable to women and healthcare professionals; (2) whether this approach can identify women at above-population level risk of breast cancer who would otherwise not have been identified and so not had access to risk-reducing options; and (3) the costs associated with implementing proactive multifactorial breast cancer risk assessment in women under 50 within general practice. Study registration number This study is listed on the ISRCTN registry. The registration number is ISRCTN17376192.